Эксергетический метод и его приложения - Бродянский Виктор Михайлович (Энергоатомиздат, 1988)
Экземпляры: КХ (20121203) / Инвентарный номер: 914101 / Цена: 5.80 / Сис.шифр: 621 / Авт.знак: Б 88 / ГРНТИ: 44.31 / ББК: 31